2008
DOI: 10.1111/j.1745-6606.2008.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Influence and Teens’ Attitude toward Online Privacy Protection

Abstract: This study examines the impact of parental influence on teens’ attitude toward privacy protection. Survey data show that teens high in concept‐oriented family communication tend to engage in discussion mediation, which, in turn, affects their level of privacy concern. In contrast, teens high in socio‐oriented communication tend to have more family rules and surf the Internet with parents. Rulemaking mediation is not directly related to teens’ level of privacy concern, while cosurfing mediation is related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 56 publications
6
72
0
3
Order By: Relevance
“…While active mediation is more helpful, both types of mediation can be used effectively and appropriately to protect children and adolescents. These results are consistent with findings in a majority of previous studies (Fujioka & Austin, 2002;Nathanson, 1999;Shin, Schriner, & Cho, 2009;Youn, 2008).…”
Section: Poor Parent-adolescent Bond and Relationshipsupporting
confidence: 95%
“…While active mediation is more helpful, both types of mediation can be used effectively and appropriately to protect children and adolescents. These results are consistent with findings in a majority of previous studies (Fujioka & Austin, 2002;Nathanson, 1999;Shin, Schriner, & Cho, 2009;Youn, 2008).…”
Section: Poor Parent-adolescent Bond and Relationshipsupporting
confidence: 95%
“…This is similar to concept-oriented communications (Moore and Moschis 1981;Moschis 1985), where debate through open discussion of ethical issues is encouraged and furthers children's own critical thinking about online issues (Carlson et al 1990, Laczniak et al 1995. For example, research has shown that teens' discussion with their parents leads to higher levels of privacy concern (Youn 2008). In such a permissive and encouraging environment, children are likely to explore the Internet more and be exposed to more unethical activities as they develop their own sense of what is right and wrong in discussion with their parents.…”
Section: Encouraging Verbalization Parenting Stylementioning
confidence: 95%
“…This makes them prone to limit their children's access to outside influences, such as media and the Internet, because they can consider these external influences as threats to parental authority (Fujioka andAustin 2002, Rose et al 1998). Indeed, teens with socio-oriented communication are more likely to have family rules and surf the Internet with parents (Youn 2008).…”
Section: Protective Parenting Stylementioning
confidence: 99%
“…Anababa ilgisi/yakınlığı ile ilişkili olarak, bazı çalışmalarda çocukların internet kullanımı ile ilgili ailelerine soru sorabilecekleri ortam sağlamaya işaret edilmektedir (Fleming ve diğ., 2006). Ayrıca, interneti güvenli kullanma konusunda anababa çocuk arasındaki açık iletişimin önemine (Youn, 2008) ve ailenin çocuğu ile birlikte internette olmasına ya da çocuğuna girebileceği siteler konusunda önerilerde bulunmasının olumlu sonuçlarına vurgu yapılmaktadır (Lee & Chae, 2007).…”
Section: İnternet Kullanımına Yönelik Anababalık Stilleriunclassified
“…Bu bulgu genel olarak alanyazınla benzerlik göstermemektedir. Önceki çalışmalarda interneti güvenli kullanma konusunda anne baba çocuk arasındaki açık iletişimin önemine (Youn, 2008) ve ailenin çocuğu ile birlikte internette olmasına ya da çocuğuna girebileceği siteler konusunda önerilerde bulunmasının olumlu sonuçlarına vurgu yapılmaktadır (Lee & Chae, 2007). Ergenlik dönemindeki katılımcılarla yapılan çalışmalarda da internet kullanımı konusunda çocukla iletişim kurmak gibi aktif anababalık stratejilerinin ergenlerin medya kullanımını sınırlandırmak ya da kural koymaktan daha etkili olduğu gösterilmiştir (Nathanson, 2002;Nathanson & Cantor, 2000).…”
Section: Tartişma Ve Sonuçunclassified